Pengaruh Audit Kinerja dan Pengendalian Intern Terhadap Kinerja Perusahaan Daerah Air Minum (PDAM) Kota Gorontalo Dengan Good Corporate Governance Sebagai Variabel Intervening - Arifin, Arifin (Bongaya Journal of Research in Accounting (BJRA), 2018)
This research aim to to know how relation make an audit of performance with Control of intern; how influence make an audit of internal control and performance either through parsial and also by simultan to governance corporate good; and how influence make an audit of performance, internal control and of good governance corporate either through parsial and also by simultan to performance of PDAM Town of Gorontalo. Sampel selected pursuant to sampling purposive counted 20 responder people at middle management level of to to the. Data collecting methode the used is observation, and interview of kuesioner. Data analysed with model estimate equation of simultan. Result of research indicate that there are positive relation and signifikan make an audit of performance with internal control, there are positive influence and signifikan make an audit of internal control and performance either through parsial and also by simultan to good governance corporate, there are positive influence and do not signifikan make an audit of performance to performance of PDAM Town of Gorontalo and internal control have an effect on and negativity of signifkan to PDAM Town of Gorontalo, but good governance corporate have an effect on positive to performance of PDAM Town of Gorontalo.